9p-12=8p

Simple and best practice solution for 9p-12=8p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9p-12=8p equation:


Simplifying
9p + -12 = 8p

Reorder the terms:
-12 + 9p = 8p

Solving
-12 + 9p = 8p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-8p' to each side of the equation.
-12 + 9p + -8p = 8p + -8p

Combine like terms: 9p + -8p = 1p
-12 + 1p = 8p + -8p

Combine like terms: 8p + -8p = 0
-12 + 1p = 0

Add '12' to each side of the equation.
-12 + 12 + 1p = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 1p = 0 + 12
1p = 0 + 12

Combine like terms: 0 + 12 = 12
1p = 12

Divide each side by '1'.
p = 12

Simplifying
p = 12

See similar equations:

| x-50.5=-16.9 | | 9(1+4n)=-279 | | 4-11b=15 | | 1/z=12/10z-8 | | g-9/9=4/9 | | 3y-5d=5d-4 | | 13+3s=-47 | | 6r+27=30 | | (x-2)(3x-12)=0 | | k-8/2=12 | | 13/8m=1/2 | | -5/2*=34 | | -2m/3=-12 | | 5(x+20)=3x+180 | | 3a-8=-6+8 | | 22=6c | | 8(-2x-4)+13=-52 | | x^4+4x^3 -x^2 +16x-20=0 | | 3a+9=4a-1 | | x^3-2x^2+5x-2=0 | | X-2/5=3/x | | 7+0.6y=19 | | 8x=26-50 | | 2x+16=130 | | 89-2x=6x+8 | | 3x+5-9=9 | | 4.2x=-4(0.62-1.2) | | 9x+40=3x+4 | | d-7=524 | | t/7.5=4 | | t/7.5-4 | | -21=n+3-5n |

Equations solver categories